Main psycho anthropological conceptions as a reference for the professional activity of psychologist - García Vega, Luis (1999)
The article the usual lineaments of 5 theoric models proceeding of the psychology what in the actuality be use for to sketch or man. It's are the models: Conductist, Psychoanalist, Humanist, Materialist, Cognitive and Emotional Cognitive. In alls the cases be present or the principals representantings be to signal the histories antecedents of each model and the type of describe which development. Finally be present the specific bibliography for each model.